Parkinson disease: Serotonin reuptake inhibitors for depression in PD - Pérez Lloret, Santiago (2012)
A recent study to investigate the safety and efficacy of serotonin reuptake inhibitors suggests that these drugs are beneficial for the treatment of depressive disorders in Parkinson disease. Whether these treatments will offer such benefits in the long term compared with other pharmacological and nonpharmacological approaches remains to be determined.